Involvement of School Committee In Budgeting Control: A Case Study At Primary School Bani Hasyim Malang Indonesia - Yoyok Amirudin; Jainudin; Zobi Mazhabi (Edukasia Islamika, 2022)
This research objective is to discuss how the involvement school committee in budgeting control. In the private school, some of the finances came from parents. The parent is the primary teacher’s partner in collaboration with the school programs. They were joined in the school committee to catch on to the school budgeting. The education system obligated schools to report the school budgeting upon approval school committee. The research subject consisted of understanding the role policy of the school committee and how far the school committee is involved in the budgeting control. This research design was field research with a descriptive qualitative approach. The data has been collected by interviewed teachers, school principals, and school committees. The result showed that the school committee in Bani Hasyim primary school Malang Indonesia was involved in budgeting control. They were actively with schools to discuss once three months, in the beginning, year to make a plan and budget together with the school.